Development of Mosque-Based Religious Tourism at Masjid Agung Central Java - Najahan Musyafak; Saerozi, Saerozi (Journal of Islamic Management, 2024)
Religious tourism destinations in the area of Masjid Agung Jawa Tengah are; al-husna tower, electric umbrella, giant Qur'an, giant drum, unique architecture, Islamic da'wah radio studio 107.9 FM, Central Java Islamic Development Museum, office hall (office space), viewing binoculars, convention hall, souvenir shop and food court, digital library, graha Agung (lodging), all of them are in good condition and worth visiting. The development of religious tourism at the Masjid Agung Jawa Tengah is carried out by increasing the development of tourism products and tourist attractions. Organizing a program of religious study activities at the Masjid Agung Jawa Tengah by inviting well-known religious figures. Optimizing the attractiveness conditions of religious tourism objects, maintaining and improving cleanliness and security conditions, as well as promotion via the internet and print media.